Upaya Penerapan Kedisiplinan dan Tanggung Jawab Pada Anak Usia Prasekolah di Pondok Pesantren Az-Zikro - Fitri, Tarisa; Itryah, Itryah (Innovative: Journal Of Social Science Research, 2025)
Character education in preschool children is a very important foundation in shaping their personality and morality for the future. Az-Zikro Islamic Boarding School, as a religious-based educational institution, plays a strategic role in instilling the values ​​of discipline and responsibility from an early age. This study aims to identify efforts made in implementing discipline and responsibility in preschool children at Az-Zikro Islamic Boarding School, as well as factors that support and hinder the implementation of these values. The research method used is a qualitative approach that includes observation techniques, direct practice, and documentation. The results of the study showed that the implementation of discipline was carried out through routine activities, such as congregational Duha prayer before entering the classroom, following the rules at the Islamic boarding school, and direct guidance from the caregiver. Meanwhile, responsibility was instilled through simple tasks, such as maintaining classroom cleanliness, tidying up seats after studying, and completing assigned tasks. Factors that support the implementation of these values ​​include a conducive Islamic boarding school environment, active involvement of ustadz and ustadzah, and support from parents. However, there are several challenges faced, such as differences in children's backgrounds, limitations of caregivers in providing individual attention, and the process of children adapting to new environments. With the right strategy and approach that suits the characteristics of preschool children, the application of discipline and responsibility values ​​can be implemented more effectively, so as to form independent and responsible individuals in the future.